Perbezaan sikap dan kecenderungan tingkah laku pencarum Kumpulan Wang Simpanan Pekerja (KWSP) terhadap penamaan wasi - Mohd Musa Sarip,; Mohd Mustaffa Mohd Jusoh @ Yusoff, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
The purpose of this article is to identify the differences in attitude and the tendency of the Employees Provident Fund (EPF) contributors in nominating wasi (executor) based on factors such as monthly income, level of education and marital status. This is an exploratory study that utilizes questionnaire as the research instrument. A total of 566 Muslim EPF contributors in Selangor have been selected as the research samples (purposive). Data are processed and analyzed using IBM statistical software, SPSS version 20. The attitudes towards the nomination of executor have been identified to include three elements namely; the attitude in the appreciation of goodwill, the attitude towards the sense of responsibility and attitude in the technical sense. However, the tendency in action or behaviour is represented by one element only. The findings show that there is a difference between attitudes and tendency in the nomination of executor among Muslim contributors with regard to marital status. The findings also show that there is a significant difference in attitude among the contributors with regard to monthly income while for the tendency of action there is a significant difference with regard to the level of education. Contributors who are already married have a more positive attitude towards the nomination of executor and they indicate a higher tendency to nominate executor compared to contributors who are still single. This could be influenced by the contributors’ experience and sources of information that they are exposed to, in addition to other factors such as having children and experiencing an unstable level of health.